(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2017)
Homogeneous discharges are easily obtained at atmospheric pressure in dielectric barrier discharges (DBD) for some noble gases. To predict the discharge electrical comportment, one-dimensional fluid model of typical DBD is presented and applied to Helium and Argon discharges. The first two moments of Boltzmann equation (continuity and momentum (drift-diffusion approximation)) are coupled with Poisson’s equation by the finite element method (FEM) using COMSOL Multiphysics software. In this work, the simulation is carried out using the same operating conditions for helium and argon gases. The electrical characteristics of the DBD, simulated by the proposed model, allow, by simple calculations, the access and the analysis of other discharge parameters such as Lissajous figures, consumed power and charge density. The obtained characteristics are assigned to the largely explained homogeneous discharges and are consistent with the experimental ones reported in the literature for both gazes. The effect of gas spacing and applied frequency on the electric characteristics has been also investigated. It has been found that for the considered range of frequency (25-200 KHz) and gap distance (2-5 mm); only one current peak is observed. The results indicate that increasing gas space or decreasing applied frequency lead to a diminishing in pulse intensity and a rise breakdown voltage.